Icons of Faith: Understanding the Connection Between Religious Symbols and Youth Happiness in Pakistan - Siddique, Ali Raza; Saleem, Muhammad (Journal of Development and Social Sciences, 2025)
This study is aimed to explore the religious symbols and their connections to the happiness among youth in Pakistan. Qualitative research design was explored the cultural components linked with religious symbols causes wellbeing of the youth. Pakistan people are emotional in terms of religious affiliations and are facing serious problems in terms of religious intolerance and terrorism. So this study focused on the importance of these symbols, which facing the hardships and their connection with resilience and coping strategies through qualitative lense. The in-depth interviews followed by thematic analysis was done to collect the data for research from youth of Pakistan. The findings shows that religious symbols give sense of direction to the youth and community accompanied by the emotional support. All these components showed that there is valuable effect of religious symbols on the happiness and contentment. This also emphasizes the vital role of cultural and religious bases among youth in order to comprehend their psychological well-being, happiness, resilience and coping strategies.